Produksi Tanaman Selada (Lactuca Sativa) Dengan Variasi Pupuk Organik Cair Pada Sistem Hidroponik - Mara Antero Siregar; Najla Lubis; Ruth Riah Ate Tarigan (Jurnal Nasional Teknologi Komputer, 2025)
Lettuce (Lactuca sativa L.) is a horticultural crop with high nutritional content and economic value, offering good prospects for cultivation. It is a seasonal plant that is easy to grow on various types of land and has a broad market demand. This study aimed to determine the production response of lettuce to different types and concentrations of ecoenzyme-based liquid organic fertilizer (POC). The research used a factorial Completely Randomized Design (CRD) with two factors and three replications. The first factor was the type of POC with five treatments: P0 = AB Mix (control), P1 = Pure Ecoenzyme (EE), P2 = EE + eggshell + pineapple, P3 = EE + moringa + insulin plant leaves, P4 = EE + guava + sweet potato + long bean leaves, and P5 = EE + water spinach + young corn. The second factor was the concentration of ecoenzyme (E0 = 0%, E1 = 25%, E2 = 50%). Observed parameters included plant height, number of leaves, fresh weight per plant, stem diameter, plant weight per plot, and root length. The results indicated that P5 (EE + water spinach + young corn) performed well and ranked second after the AB Mix across most parameters. This suggests that diverse organic ingredients in liquid fertilizers can support optimal lettuce growth, making them a promising alternative to chemical fertilizers.